2007
DOI: 10.1210/en.2006-0918
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenic Loss of Brown Adipose Tissue Sensitivity to β-Adrenergic Stimulation in the Ovine

Abstract: In ruminants and other large animals, expression of uncoupling protein-1 (UCP1) in brown adipose tissue (BAT) is confined to the perinatal period when it plays a key role in nonshivering thermogenesis. This study determined whether loss of expression of the BAT phenotype was due to reduced response to a beta-agonist, isoprenaline, and expression of the peroxisome proliferator-activated receptor (PPAR) family [PPARalpha, PPARgamma, PPAR coactivator 1alpha (PGC-1alpha)], which regulates UCP1 gene expression. Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 39 publications
(53 reference statements)
5
48
0
Order By: Relevance
“…2H, where BAT from FPLD animals displays a white-like appearance. This phenomenon has been observed in genetically manipulated animal models (30,31) and in humans with a reduced potential of adipose precursor cells (32).…”
Section: Fpld Mice Are Unable To Accumulate Fatmentioning
confidence: 78%
“…2H, where BAT from FPLD animals displays a white-like appearance. This phenomenon has been observed in genetically manipulated animal models (30,31) and in humans with a reduced potential of adipose precursor cells (32).…”
Section: Fpld Mice Are Unable To Accumulate Fatmentioning
confidence: 78%
“…We have previously demonstrated that replacement of BAT with WAT in newborn lambs is due to down-regulation of adrenergic induced Ucp1 activation and repression of Pgc-1␣ expression (7). The question as to whether mature adipocytes can "interconvert" or whether separate pools of white and brown progenitor cells mediate "transdifferentiation" of these tissues has not been resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Transdifferentiation from white to brown adipose tissue and/or vice versa has been reported in many species, including rodents, cats, dogs, ruminants (2)(3)(4)(5)(6)(7)(8)(9), and humans (10). Studies have suggested the existence of brown adipocytes in humans not only at birth but also within white fat depots in adult humans (11).…”
mentioning
confidence: 99%
“…In cattle and sheep at birth, the different AT depots, except for the subcutaneous depot in some bovine breeds , can be considered as brown due to the high expression of UCP1, cytochrome c oxidase and ADP/ATP carrier protein (Casteilla et al, 1987;Casteilla et al, 1989). UCP1 mRNA reaches its highest level in the various BAT at birth and is no longer detectable 2 days later in cattle (Casteilla et al, 1987), and sheep, probably as the result of a sharp decline in the expression of peroxisome proliferatoractivated receptor-a (PPARa) and peroxisome proliferatoractivated receptor-c coactivator-1a (PGC-1a) (Lomax et al, 2007). In cattle, since the estimated number of cells remains constant during the first week following birth, it has been thought that a transdifferentiation of brown into white adipocytes occurs.…”
Section: Dynamics Of At Growthmentioning
confidence: 99%